Thermoluminescence characterization of smartphone screen for retrospective accident dosimetry - Siti Rozaila, Z.; Khandaker, Mayeen Uddin *; Norfadira, W.; Mohd Khairul, H. A. J.; Abdul Sani, S.F.; Bradley, D.A. * (Elsevier, 2020)
With increasing use of ionizing radiation and associated nuclear materials, concern arises regarding the possibility of harm from unplanned events, both to the surrounding environment as well as to its inhabitants; the Three Mile Island, Chernobyl and Fukushima Daiichi nuclear power plant incidents come to mind. Retrospective dosimetry can provide estimation of the radiation dose received from such accidents, the information allowing appropriate remedial measures to be formulated. In the affected area a number of objects can be applied as natural dosimeters. Given that the mobile phone is a device used by a large fraction of the population, investigation has been made of the suitability of the phone screen for retrospective dosimetry. Samples of five brands of phone screen were studied (Iphone, Sony, Samsung, Asus and Xiomi), investigating key thermoluminescence (TL) properties, including TL dose response, glow curves, reproducibility and long-term stability of the TL signal. Within the γ-radiation dose range up to 10 Gy, these parameters show the Iphone screen to offer best use as a suitable material for retrospective dosimetry. Reconstruction of absorbed dose is possible for a period of up to four weeks post-incident. One proviso concerns the ability to adequately correct for TL signal loss during this time.